The philosophy of Maqasid al-Shari’ah and its application in the built environment - Ahmad Sarkawi, Azila; Abdullah, Alias; Md. Dali, Norimah; Khazani, Nur Amilin (Journal of Built Environment, Technology and Engineering (JBETE), 2017)
This paper deciphers the application of the philosophy of the Maqasid al-shari’ah (Objectives of Islamic Law) in the built environment. Being seen as a result of human minds and acts towards the environment for the purpose of human needs, wants and values, the built environment is very much related to the Islamic theory of man as vicegerent (khalifah) on earth. Here lies the interconnectedness between the built environment and the Maqasid al-shari’ah. In this regard, the terms Islam and Maqasid al-shari’ah play the same role in the sense that they set a way of life for mankind with the principles of the Qur’an and Sunnah. Human reactions in their daily life basically react upon these elements. Definitely, human wellbeing or maslahah (public interests) for mankind is the ultimate aim of the shari’ah. Thus this paper attempts to assimilate the philosophy of the Maqasid al-shari’ah with the built environment’s profession towards the realization of their role as khalifah. Ultimately, this will pave for better human interaction with the environment resulting in utmost quality of the built environment for human life.